History of formation and development of the Karaganda State Technical University - Nurligenova, Z.N. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The article deals with the history of formation and development of the Karaganda State Technical University, the opening of which is associated with the development of the productive forces of Kazakhstan in the postwar fifties, as well as increased demand for coal and other mineral resources in connection with the construction of the giants of black and nonferrous metallurgy and the discovery of promising new deposits of iron, copper and other ores in the Central-Kazakhstan region. The purpose of this scientific article was to study the history of the formation and development of the Karaganda State Technical University on the basis of archival documents. The objectives of the presented scientific work is to study the state of the educational and material base of the Karaganda Mining Institute, scientific and pedagogical and educational work carried out in the team, as well as the creation of new departments, laboratories, selection and placement of teachers, scientists. The number of students and teaching staff of the Institute is tracked. Special attention is paid to the Hero of Socialist Labor, twice laureate of the State Prize of the Kazakh SSR, academician of MSE RK Abylkasym Saginovich Saginov, who stood at the origins of the Institute and was a rector of the more than thirty years. A.S. Saginov made a significant contribution to the development of the mining industries of Kazakhstan, as well as to the training of highly qualified specialists. The relevance of the study is due to the complex tasks of modernization of the system of higher technical education in modern Kazakhstan. Modernization of technical education, being one of the progressive ideas of the pedagogical picture of the world, is activated in national education, as a rule, at the turn of the century, when the tense present becomes the boundary between the traditional «past» and the emerging «new». Consequently, in the period of modernization in education, there is an awareness of the need for methodological changes, the search for new teaching methods, the expansion of the social base and the creation of higher level educational institutions. These processes of «boundary pedagogy » can be traced in the projects of modern educational reforms on the example of the Karaganda State Technical University.
Қарағанды мемлекеттік техникалық университетінің қалыптасу жəне даму тарихы
История становления и развития Карагандинского государственного технического университета
Keywords: higher technical school; the Karaganda State Technical University; students; teaching staff; highly qualified engineers; Central Kazakhstan region; Kazakhstan